THE ONTOLOGICAL CAPTURE OF REASON AND REVELATION: TOWARD A SYNTHESIZING APPROACH OF IBN ‘ARABĪ AND MULLĀ ṢADRĀ - Musa Alkadzim (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2023)
Reason and revelation are a topic that is debated by many parties to determine the position and superiority between reason and revelation. There are differences of opinion among thinkers regarding the position of reason and revelation. This debate has also attracted the attention of many Islamic thinkers, including Islamic philosophers. This paper explores the ontological capture of reason and revelation debate by two of the most prominent Sufi philosophers, Ibn ‘Arabī and Mullā Ṣadrā. This research employs a literature review as a research methodology, with an emphasis on synthesis and integration. Through this research, it can be concluded that Ibn ‘Arabī’s and Mullā Ṣadrā’s ontological perspectives have deconstructed theological and epistemological disagreements between rationalists who place reason above revelation and their traditionalist opponents. Ibn ‘Arabī’s theory of creative imagination unveils the ontological order of reason and revelation, whereas Mullā Ṣadrā’s theories of tashkīk (gradation of being) and the union of the knower and the known during the production of knowledge (or to be more precise, the union of intellect and intelligible during intellection) consistently place reason and revelation not in opposing sides but rather in a single gradational existence. Both Ibn ‘Arabī and Mullā Ṣadrā have broken the theological and epistemological vicious cycle by introducing ontological interventions into the debate. Ibn ‘Arabī and Mullā Ṣadrā may or may not have intended to participate in the polemic; as a result, these outcomes were rarely mentioned in the historical context of the ideas.